Quantifying Poincare's Continuation Method for Nonlinear Oscillators. (17th August 2015) - Núñez, Daniel; Rivera, Andrés
Abstract : In the sixties, Loud obtained interesting results of continuation on periodic solutions in driven nonlinear oscillators with small parameter (Loud, 1964). In this paper Loud's results are extended out for periodically driven Duffing equations with odd symmetry quantifying the continuation parameter for a periodic odd solution which is elliptic and emanates from the equilibrium of the nonperturbed problem.